2018
DOI: 10.1111/echo.14147
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional transesophageal echocardiography is an attractive alternative to cardiac multi‐detector computed tomography for aortic annular sizing: Systematic review and meta‐analysis

Abstract: Background Cardiac imaging is the cornerstone of the pretranscatheter aortic valve replacement (TAVR) assessment. Multi‐detector computed tomography (MDCT) is considered the conventional imaging modality. However, there is still no definitive gold standard. Targeted cohort of inoperable high‐risk patients with underlying comorbidities, particularly renal impairment, makes apparent the need for MDCT alternative. We aimed to demonstrate the correlation extent between MDCT and three‐dimensional transesophageal ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
(148 reference statements)
0
8
0
Order By: Relevance
“…To the best of the authors’ knowledge, the two previous studies have attempted to methodically compare 3D-TEE and MDCT for TAVR sizing in the same patient population [ 60 , 61 ]. Both studies, however, basically used the 3D-TEE manual technique for annular measurements.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of the authors’ knowledge, the two previous studies have attempted to methodically compare 3D-TEE and MDCT for TAVR sizing in the same patient population [ 60 , 61 ]. Both studies, however, basically used the 3D-TEE manual technique for annular measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown good correlation between 3D annular and perimeter measurements of the aortic annulus compared to CT. In a meta-analysis by Elkaryoni and colleagues including 14 studies and 1,228 patients, there was excellent agreement between 3D TEE annular area and perimeter with CT-derived measurements (r > 0.8) [28] .…”
Section: Aortic Valvementioning
confidence: 90%
“…Valve area immediately after repair can also be accurately assessed by 3D planimetry [42] . Multiplanar reformatting (MPR) is used for linear annular measurements of the tricuspid and mitral valves [47,48] and aids in the periprocedural sizing of rings and valves, sizing of ASDs, sizing of LAA for LAA closure devices, and valve sizing for transcatheter valve replacement [28,49,50] . 3D TEE has been shown to have increased accuracy compared to 2D echo which in many cases is relevant for improved clinical outcomes.…”
Section: Perioperative 3d Tee For Procedures Guidance and Valvular Assmentioning
confidence: 99%
“…Equivalence with annular measurements obtained by multidetector CT (MDCT) has been demonstrated consistently with a strong linear correlation between the two modalities for annular area (r = .86) 9 and perimeter (r = .85). 10 The proviso being that 3D TEE predictably undersizes with respect to MDCT (mean difference −2.2 mm 2 in the largest meta-analysis). [9][10][11] As measurements are performed on static images, spatial resolution can be prioritized over temporal resolution, being mindful of the necessary trade-off between frame rate and line density.…”
Section: Comparison With Cross-sectional Imagingmentioning
confidence: 98%
“…10 The proviso being that 3D TEE predictably undersizes with respect to MDCT (mean difference −2.2 mm 2 in the largest meta-analysis). [9][10][11] As measurements are performed on static images, spatial resolution can be prioritized over temporal resolution, being mindful of the necessary trade-off between frame rate and line density. The current consignment of European and American guidelines 12 do not suggest a gold standard for imaging in this area, advising that 3D TEE is appropriate for THV sizing when performed in a center with sufficient experience in the technique.…”
Section: Comparison With Cross-sectional Imagingmentioning
confidence: 98%